Analisis Sistem Traceability Produk Tuna Ditinjau Dari Aspek Supply chain PT Hatindo Makmur - Prasatia, Pande Ditha; Faiqoh, Elok; Dharma, I Gusti Bagus Sila; Pratiwi, Made Ayu (Journal of Marine and Aquatic Sciences; Vol 6 No 2 (2020)DO - 10.24843/jmas.2020.v06.i02.p14, 2020)
Indonesian tuna fisheries dominate world tuna production. One of the priority water areas as tuna fishing catchment is the Sendang Biru Aquatic area, because it has Pondokdadap Fish Landing Center and is the center of largest fishing activity in Malang. The international market wants a guarantee of high quality and food safety, this is supported by the implementation of traceability systems. Own traceability is way to guarantee food quality by tracking information about the position of product. The purpose of this study is to describe the supply chain system of PT Hatindo Makmur, describe the readiness to implement traceability, and develop a strategy to support the implementation of traceability. The method used is a survey and questionnaire using descriptive analysis. The results of the analysis show that the Supply chain system is carried out by several parties fishermen, PPI Pondokdapdap, CV Berkah Alam, and PT Hatindo Makmur. The readiness of fishermen in Sendang Biru the implementation of traceability systems is categorized as ready with a percentage of 79%. The strategy that can be implemented is optimize the use of tuna resources, develop a simple traceability system for handling, collaborate with NGOs to socialization and training traceability and application to fishermen, use  modern technology in recording and managing permits, Providing incentives to fishermen from companies to follow regulations, monitoring and controlling fishing activities, developing owned facilities to manage ship registration and licensing at ports, increasing socialization of the importance of catch data to the results of the sale.